The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s10439-015-1506-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping 3D Strains with Ultrasound Speckle Tracking: Method Validation and Initial Results in Porcine Scleral Inflation

Abstract: This study aimed to develop and validate a high frequency ultrasound method for measuring distributive, 3D strains in the sclera during elevations of intraocular pressure. A 3D cross-correlation based speckle-tracking algorithm was implemented to compute the 3D displacement vector and strain tensor at each tracking point. Simulated ultrasound radiofrequency data from a sclera-like structure at unde-formed and deformed states with known strains were used to evaluate the accuracy and signal-to-noise ratio (SNR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…The marked contrast between the circumferential and meridional responses was unlikely an artifact of poorer measurement accuracy in one in-plane direction than the other, because the circumferential or meridional direction was not strictly aligned with any scanning directions, i.e., both were scanned as lateral and elevational depending on the location. Our validation studies showed that the strain measurement accuracy was similar for the two in-plane directions [22]. Previous surface strain measurements have reported very small circumferential strains ($0.5%) in human donor eyes when inflated to a higher IOP [10,26].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The marked contrast between the circumferential and meridional responses was unlikely an artifact of poorer measurement accuracy in one in-plane direction than the other, because the circumferential or meridional direction was not strictly aligned with any scanning directions, i.e., both were scanned as lateral and elevational depending on the location. Our validation studies showed that the strain measurement accuracy was similar for the two in-plane directions [22]. Previous surface strain measurements have reported very small circumferential strains ($0.5%) in human donor eyes when inflated to a higher IOP [10,26].…”
Section: Discussionsupporting
confidence: 64%
“…We implemented a data acquisition system with automated 3D imaging and synchronized data storage, and a 3D speckle tracking algorithm that determines the 3D displacement vectors for tissue grid points within the scanned volume and reconstructs the full strain tensor from the displacement gradients. We performed validation studies to analyze the displacement and strain accuracy of the 3D method [22]. Simulated whole voxel and subvoxel displacements in the presence of simulated random electrical noise showed an absolute error less than 0.01 voxel in all scanning directions for 0, 0.5, 1, and 2 voxel translations.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, ultrasonagraphy has been used to visualize the whole eye, however it is limited by rather low resolution and low contrast (Kilker et al, 2014; Lorente-Ramos et al, 2012). High frequency ultrasound designed for small animal imaging has recently been used to measure deformations of the porcine sclera in an ex vivo inflation test, however high frequency ultrasound lacks the depth penetration to study a whole eye from a large animal (Cruz Perez et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…More importantly, it precludes the study of dynamic events such as pressure-induced deformations, which are essential to understand eye biomechanics and the role of collagen. [14][15][16] Extending PLM imaging from thin sections to thick ocular tissues is thus desirable. However, imaging thick tissues is complicated by strong tissue scattering.…”
Section: Introductionmentioning
confidence: 99%